High-Voltage Equipment of Power Systems Design, Principles of Operation, Testing, Monitoring and Diagnostics - Ushakov, V. Ya. specialist in the field of electric power engineering Professor of Tomsk Polytechnic University, Doctor of technical sciences 1939- (Power Systems, 2023)
This textbook covers in detail the problem of improving the reliability and service life of high-voltage equipment in electric power systems, mainly through testing, monitoring, and diagnostics, which support the timely repair or replacement of equipment. The main focus is on high-voltage power and instrument transformers, switching devices, powerful rotating electric machines, capacitors, bushings, and power cables.The design, purpose, and principle of operation for each respective type of equipment, as well as adverse factors that can lead to defects (primarily in insulation) - and, as a result, to accelerated aging (wear) and failure - are considered.In turn, the scientific and technological foundations and practical application of testing, monitoring, and diagnostics to determine the technical condition of equipment are described. Considerable attention is paid to new and promising methods for testing under voltage (without interrupting operation) - such as pulsed flaw detection and dielectric spectroscopy. In addition, the authors propose a number of helpful physical concepts and technical solutions.The book stands out in terms of the breadth and depth of the consideration of the problem, which reflects recent trends and concepts for the development of the electric power industry, and its convincing demonstration of the capabilities of traditional and advanced methods in relation to the main equipment used in electric power systems.The textbook is intended for undergraduate and graduate students in the field of high-voltage technologies for electric power systems. It also benefits engineering personnel working with electric power systems and in the electrical industry.